A systematic review of non‐surgical treatments for lentigo maligna. (24th August 2015) - Read, T.; Noonan, C.; David, M.; Wagels, M.; Foote, M.; Schaider, H.; Soyer, H. P.; Smithers, B. M.
Abstract: Lentigo maligna (LM) is the most common melanocytic malignancy of the head and neck. If left untreated, LM can progress to lentigo maligna melanoma (LMM). Complete surgical excision is the gold standard for treatment, however, due to the location, size, and advanced age of patients, surgery is not always acceptable. As a result, there is ongoing interest in alternative, less invasive treatment modalities. The objective was to provide a structured review of key literature reporting the use of radiotherapy, imiquimod and laser therapy for the management of LM in patients where surgical resection is prohibited. An independent review was conducted following a comprehensive search of the National Library of Medicine using MEDLINE and PubMed, Embase, Scopus, ScienceDirect and Cochrane Library databases. Data were presented in tabular format, and crude data pooled to calculate mean recurrence rates for each therapy. 29 studies met the inclusion criteria: radiotherapy 10; topical imiquimod 10; laser therapies 9. Radiotherapy demostrated recurrence rates of up to 31% (mean 11.5%), with follow‐up durations of 1–96 months. Topical imiquimod recurrence rates were up to 50% (mean 24.5%), with follow‐up durations of 2–49 months. Laser therapy yielded recurrence rates of up to 100% (mean 34.4%), and follow‐up durations of 8–78 months. in each of the treatment series the I 2 value measuring statistical heterogeneity exceeded the accepted threshold of 50% and as such a meta‐analysis of included data were inappropriate. For non‐surgical patients with LM, radiotherapy and topical imiquimod were efficacious treatments. Radiotherapy produced superior complete response rates and fewer recurrences than imiquimod although both are promising non‐invasive modalities. There was no consistent body of evidence regarding laser therapy although response rates of up to 100% were reported in low quality studies. A prospective comparative trial is indicated and would provide accurate data on the long‐term efficacy and overall utility of these treatments.